Kajian Sebaran Humus, Alofan dan Senyawa Humus Kompleks Pada Tanah Andisol - Kusmiyarti, Tati B.; Mega, M.; Dibia, N.; Widyarshana, D.O. (Universitas Muhammadiyah Yogyakarta, 2005)
Humic substances (humus), allophanes and humus complexes are the soil component which have highly reactivity and give great contribution on genesis and lead to presence of specific chemical and physical properties of Andisols. The study on humus, allophanes and humus complexes was conducted on Andisols in Tawangmangu Karanganyar District of Central Java and Bedugul, Tabanan District of Bali to observe the distribution of humus, allophanes and humus complexes along the profile and the factor affected its distribution. The result showed that the content of humus complexes tend to decrease with the dept in accordance to the content of humus, on the contrary of the content of allophanes. So the humus complexes are abundance on the upper layer whereas the allophanes on the lower layers of the profiles. By means of the regression calculation indicated that both of the pH (H2O) of the soil and the content of humus are controlled the formation of humus complexes and I or allophanes along the profiles.